2003
DOI: 10.1063/1.1610441
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional infrared correlation spectroscopy as a probe of sequential events in the diffusion process of water in poly(ε-caprolactone)

Abstract: In this study, the diffusion process of water molecules in poly͑-caprolactone͒ ͑PCL͒ has been investigated using in-situ attenuated total reflection Fourier transform infrared ͑ATR-FTIR͒ spectroscopy. In our system, the original broad water OH bands in 1D IR spectra can be effectively differentiated into four bands, located at 3641, 3593, 3410, and 3203 cm Ϫ1 , respectively, using 2D correlation analysis. The bands at 3641 cm Ϫ1 ͑antisymmetric͒ and 3593 cm Ϫ1 ͑symmetric͒ are assigned to the OH stretching vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…At first glance, it would appear that the latter channel would be dominant, as solvent filtration through the capillary wall is limited by a very low diffusion coefficient (D s $ 10 À13 Ä 10 À12 m 2 /s). 59 However, when accounting for the ratio of meniscus to capillary wall surface areas, it can be concluded that solvent evaporation at the meniscus surfaces bears limited influence on evaporation kinetics, while solvent filtration through the capillary wall controls the process in question. The process can be described by the following set of equations and boundary conditions.…”
Section: Postprocesses Relaxation In Electrospun Nanofibersmentioning
confidence: 99%
“…At first glance, it would appear that the latter channel would be dominant, as solvent filtration through the capillary wall is limited by a very low diffusion coefficient (D s $ 10 À13 Ä 10 À12 m 2 /s). 59 However, when accounting for the ratio of meniscus to capillary wall surface areas, it can be concluded that solvent evaporation at the meniscus surfaces bears limited influence on evaporation kinetics, while solvent filtration through the capillary wall controls the process in question. The process can be described by the following set of equations and boundary conditions.…”
Section: Postprocesses Relaxation In Electrospun Nanofibersmentioning
confidence: 99%
“…As is well known, the water molecules form hydrogen bonds, the water OH stretching vibration band will shift to a lower wavenumber compared to that of free water [32,33]. Thus, the band appears at 3373 cm À1 due to the n as mode of strongly hydrogen-bonded water molecules [29]; the absorption band at 3560 cm À1 is the vibrations of moderately hydrogen-bonded water molecules with -CN group in PAN; the band at 3618 cm À1 is assigned to the vibrations of weakly hydrogen-bonded water molecules with -CN group in PAN. The sign of the cross-peaks in the asynchronous spectrum give more useful information about relative temporal relationships for different bands.…”
Section: D Correlation Analysismentioning
confidence: 91%
“…In our group, much works have been performed on the diffusion of water and small organic molecules by ATR-FTIR and 2D correlation analysis [26][27][28][29][30][31]. In this work, we monitor the diffusion process of water and CaCl 2 aqueous solution in PAN membrane by Diffusion 2D-IR Hydrogen-bonding Band fitting Association…”
Section: Introductionmentioning
confidence: 97%
“…The IR spectra, especially the 2D spectra, have already been proved to be powerful tools in the investigation of the water structures inside polymeric materials [41]. In the present study, changes in the spectra of F88 and PC88 in the range of 1800-1600 cm À1 were investigated to study the water structure changes in these two hydrogel systems during their sol-gel transitions.…”
Section: Investigation Of Waters In the Hydrogel Systems During Transmentioning
confidence: 99%